Friction self-riveting welding between polymer matrix composites and metals. (December 2019) - Meng, Xiangchen; Huang, Yongxian; Xie, Yuming; Li, Junchen; Guan, Meng; Wan, Long; Dong, Zhibo; Cao, Jian
Abstract: To construct reliable heterojunctions between metals and polymer matrix composites, friction self-riveting welding (FSRW) was proposed, characterized by multi-scale mechanical interlocking and adhesive bonding, to improve mechanical properties. Holes and porous oxide structures were pre-fabricated on the metal sheet. High-quality heterogeneous joints were achieved. Under the frictional heat and forging force, the composites were softened and flowed into the pre-fabricated holes and porous structures via squeezing behaviors from a welding tool, improving macro/micro-mechanical interlocking. The oxide layers also enhanced adhesive bonding. The maximum tensile shear strength reached 27 MPa based on multi-scale mechanical interlocking and adhesive bonding. Joint fracture located at the interfaces between composites and metals, the composites rivets and the intermixing region of fibers. This strategy has the potential to construct reliable heterojunctions between polymers or polymer matrix composites and metals in the fields of aerospace and automotive.